Walking in the Dordogne : 31 walks in the Périgord Noir (around Sarlat) and the Périgord Poupre (around Bergerac) including Rocamadour and the Gouffre de Padirac in the Lot /: 31 walks in the Périgord Noir (around Sarlat) and the Périgord Poupre (around Bergerac) including Rocamadour and the Gouffre de Padirac in the Lot. (2015) - Unknown
No abstract available